An Interfaith Perspective on Globalization for the Common Good (American Journal of Islam and Society, 2004)
The third Annual International Conference on Globalization for theCommon Good was held on 27-31 March 2004 at the Bustan Rotana hotel, Dubai, the United Arab Emirates. More than thirty participants, representingacademics, peace activists, theologians, environmentalists, and businessmenfrom the United States, Europe, Japan, the Gulf region, Australia,and South Africa attended the eleven plenary sessions. These were dividedunder the following headings: Muslim-Christian Dialogue for the CommonGood; Religions and Social Justice; Profit and the Common Good: Conflictor Convergence?; Religions and the Common Good; Urbanization andCities in a Global Age; Globalization and Civilizations; EthicalPerspectives on Globalization; Interfaith Dialogue and Peace-building;Natural Resources, Ecology and Development; Youth in a Global Age; andScience and Technology in a Global Age. The conference was officiallyopened by the founder and chief convenor of the Interfaith Perspective onGlobalization for the Common Good, Dr Kamran Mofid of the UnitedKingdom.Dr William Lesher (Lutheran School of Theology, Chicago) in his“Pathways to Peace” identified the major factors supporting globalizationand showed how global trends become indigenized through the process ofglocalization. Sister Beatrice Mariotti’s (St. Mary’s Catholic HighSchool, Dubai) “Globalization and Christian-Muslim Spiritual Dialoguein Dubai” dealt with three challenges to cultural identity: consumerism,the Internet, and isolationism. Markus Glatz-Schmallegger (CatholicSocial Academy of Austria) argued in his “Religions Acting for ‘Bridgingand Linking Social Capital’ in the Context of Globalization,” that religion,as an organ of civil society, can contribute significantly to socialcapital.In the session on “Profit and the Common Good: Conflict or Convergence?”Kamran Mofid outlined both the negative and positive aspects ofglobalization. This was followed by a lively discussion on how globalization’sbenefits could be extended to all and not confined to a minority ofindividuals, multinationals, and states. Suleman Dangor (University ofKwazulu-Natal, South Africa) outlined the positive and negative featuresof globalization, and then elaborated on the role that religions could playin ensuring that its benefits are spread equitably while developing nationsare protected from its negative impact.Jakob von Uexkull (The Right Livelihood Awards, London, UK), in his“Global Values and Global Stability,” made a case for equitable access tothe world’s natural resources. The possibility of this happening is greaternow that we are moving to a post-secular world. Keyvan Tabari emphasizedthe importance of national sovereignty. Since the demise of the USSR ...